Assessment of interrelationships among grain yield and secondary traits of early-maturing maize inbred lines under drought and well-watered conditions - Oyekunle, M.; Apraku, B.B. (2018)
nowledge and understanding of interrelationships between grain yield and yield-related traits would ensure progress from selection in maize breeding programs through the use of appropriate selection indices. One hundred and fifty-sixearly-maturing maize inbreds were evaluated at fiveenvironments in Nigeria, for 2 years to assess the relationship between grain yield and yield-related traits of maize inbreds under drought and well-watered conditions. Genotypes, and genotype × environment interaction mean squares were significant(P<0.05) for grain yield and other measured traits under drought and well-watered conditions. Under drought, plant and ear aspects, ear height, ears per plant (EPP), leaf senescence, number of seeds per ear, and seeds per row had direct effects on grain yield, accounting for 76% of total variation. Under well-watered conditions, days to silking, ear aspect, ear height, EPP, ear length, 100-kernel weight, number of seeds per row, plant height, and stalk lodging had significantdirect effects on yield. Genotype main effect plus genotype × environment interaction (GGE) biplot identifiedplant and ear aspects, days to anthesis and silking, ASI, EPP, stay green characteristic, plant and ear heights, ear diameter, number of seeds per ear, number of seeds per row, and ear length as the most reliable traits for indirect selection for grain yield improvement under both research conditions. Plant and ear aspects, ear height, stay green characteristic, number of seeds per ear, and number of seeds per row were identifiedby both path–coefficientand GGE biplot analyses as the most reliable traits for selecting for grain yield under drought. Ear aspect, EPP, days to silking, plant and ear heights, number of seeds per row, and ear length were the most reliable traits for selecting for improved grain yield under well-watered conditions.